SINGLE NUCLEOTIDE POLYMORPHISM OF ECCB5 GENE OF MYCOBACTERIUM TUBERCULOSIS COMPLEX ISOLATES FROM SUSPECTED PULMONARY TB PATIENTS IN SURABAYA INDONESIA - Kurniawati, Siti; Soedarsono, Soedarsono; Aulanni’am, Aulanni’am; Mertaniasih, Ni Made (African Journal of Infectious Diseases (AJID), 2018)
Background: Mycobacterium tuberculosis Complex (MTBC) is a group of Mycobacterium that causes tuberculosis (TB). TB is an infectious disease that remains a global health problem. Indonesia is one of the five countries in the world where TB is the most prevalent and became the country with tle second largest rate of TB in 2014 and 2015. MTBC has high pathogenicity that can cause infections in animals and humans. The most common route of transmission is via airborne droplet nuclei and contact with animals or humans infected with TB. MTBC has many virulence factors. One of these factors is EccB5 that is encoded by eccB5 gene. EccB5 is a transmembrane proteinconserved membrane protein and could play a role in inducing damage in host cells, macrophage infection, and may correlate with active disease. The characterization of eccB5 gene needs to be studied to determine the nucleotide sequences, which may be associated with active disease. The aim of this research was to analyze the nuclotide sequences of eccB5 gene of MTBC from suspected pulmonary tuberculosis patients, SNPs of eccB5 gene and possible correlation with the disease, especially in Indonesia. Materials and Methods: Samples were collected from the Tuberculosis Laboratory, Clinical Microbiology of Dr. Soetomo Hospital Surabaya Indonesia. DNA extraction used boiling extraction method and continued nucleic acid amplification using PCR techniques. Primer pairs used eccB5 SK.. The positivity of DNA specific revealed amplicon in 1592 bp. PCR product was sequenced by 1st Base (First BASE Laboratories Sdn Bhd, Selangor, Malaysia). The sequence analysis used Genetyx-Win version 10.0 (Genetyx Corporation, Tokyo, Japan). Results: Total isolates of Mycobacterium spp. were 28 and those that showed positive MTBC were 24 isolates and 4 nontuberculosis mycobacteria (NTM) using immunochromatographic test (ICT). The amount of homology from MTBC using blast NCBI was 99%-100%. Two SNPs were found in position c.1277 which revealed replacement of amino acid in 426 of codon position. Conclusion: The sequence of eccB5 gene of MTBC showed high significant homology, while proposed nonsynoymous single nucleotide polymorphisms (nsSNP) may associated with clinical outcomes. Keywords: Pulmonary Tuberculosis, Mycobacterium tuberculosis Complex, eccB5 gene, SNPs